Perioperative Hemodynamic Management and Pharmacotherapeutics of Patients Undergoing Thoracic Endovascular Aortic Repair. (29th December 2014) - Muehle, Anja; Uzun, Isil; Jalali, Ziba; Khoynezhad, Ali
Abstract : Thoracic endovascular aortic repair (TEVAR) has become an attractive alternative treatment option for many patients with specific thoracic aortic disease. New devices and advanced image-guided procedures are continuously expanding the indications and improve neurological outcomes. Hemodynamic management of these patients is a critical aspect in reducing neurological deficit and it is different compared to patients undergoing open thoracic aortic operations. There are two different phases of blood pressure management for patients with thoracic aortic disease. Before and during the critical steps of TEVAR anti-impulsive therapy facilitates safe positioning and stent deployment. After stent grafts are deployed, controlled hypertensive blood pressure levels are achieved to avoid spinal cord ischemia. This precise blood pressure strategy is essential to ensure a safe procedure and good long-term results.